Lowering of palm oil cloud point by enzymatic acidolysis - Khalid, Khazainah; Musa, Mushaireen; Jusoff, Kamaruzaman; Abdullah, Rahman; Md. Zaini, Zetty Madina; Samsudin, Azlina (IDOSI Publications, 2011)
This study was carried out to lower the cloud point value of palm oil by enzymatic acidolysis at different mole ratio of palm oil to capric acid of 1:1, 1:2, 1:3 and 1:5. Lipase 1, 3-specific from Rhizomucor miehei; lipozyme RM IM was used in this study. Cloud point value was determined using PORIM p4.3 method (1995). Results showed that by increasing the mole ratio of palm oil to capric acid resulted in the increase of cloud point value before and after acidolysis significantly (p<0.05). The cloud point value was decreased after acidolysis for each mole ratio.